Working in Digital and Smart Organizations Legal, Economic and Organizational Perspectives on the Digitalization of Labour Relations (Springer International Publishing, 2018)
Contributing to recent debate on the emergence of digital and agile work, this book explores the implications for labour and employment relations within and beyond organizational boundaries. Taking a multidisciplinary approach to the key issues and challenges of digitalization, this collection covers topics such as the gig economy, crowdworking and Industry 4.0. Theory and analysis are combined as the authors examine the impact of digital and smart work on organization, HRM and labour law. With comprehensive empirical evidence for those interested in understanding the more complex trajectories of today's transforming work relationships, this book will not only appeal to students and academics but also to policy-makers, trade unionists and employers' organizations.